The Cornett-Whitley gang: violence unleashed in Texas - Johnson, David (A. C. Greene series, 2019)
At the mustang pen in Butler's pasture -- Demonic laughter -- The headwaters of Ugly creek -- Without a single train robber -- Fiendish atrocities -- Immunity from unpleasant consequences -- A stream of fire -- I will make things lively -- Wild, wooly and hard to curry -- Prefer them dead -- Lawless and violent -- The wages of sin.